Keterpurukan Penonton Bioskop di Kota Semarang, 1979-1996 - Luluk Maknunah Fahruddin; Bambang Rakhmanto; Ufi Saraswati (Jurnal Sejarah Indonesia, 2026)
This study examines the decline in cinema attendance in Semarang City between 1979 and 1996 in relation to social, economic, and cultural changes in urban society. The study aims to describe the conditions of Semarang society during this period and to analyze the decline in cinema attendance and the factors contributing to it. The study employed historical methods, including heuristics, source criticism, interpretation, and historiography. Data sources included statistics from the Central Java Statistics Agency (BPS), contemporary newspaper archives, and interviews with informants who were involved in or experienced the cinema industry firsthand in Semarang. The results show that although the number of cinemas in Semarang continued to increase from the late 1970s to the 1980s, the number of cinemagoers tended to decline. In the 1980s, the average number of cinemagoers reached around four million per year, but in the 1990s, this number dropped drastically to around four hundred thousand per year. Various factors, such as advances in audio-visual technology, the rise of television and VCDs, the high circulation of pirated VCDs, high ticket prices, and inadequate facilities at traditional cinemas, influenced this decline. Furthermore, the dominance of modern cineplexes in the distribution of imported films and the declining appeal of national films also weakened the position of local cinemas. This situation was further exacerbated by high entertainment taxes and the 1997–1998 monetary crisis, which reduced public purchasing power. As a result, several traditional cinemas in Semarang were forced to close due to continued losses. This research shows that the decline of cinemas in Semarang is the result of changes in technology, the economy, and public entertainment consumption patterns, which have transformed cinemas' role as public entertainment spaces.